2021
DOI: 10.1002/cam4.3984
|View full text |Cite
|
Sign up to set email alerts
|

Signature based on metabolic‐related gene pairs can predict overall survival of osteosarcoma patients

Abstract: Background Osteosarcoma is a tumour of malignant origin in children and adolescents. Recent progression indicates that it is necessary to develop new therapies to improve the patient's prognosis rather than strengthen anti‐tumour chemotherapy. Researchers recently realised that cancer is a kind of disease with a metabolic disorder, and metabolic reprogramming is becoming a new cancer hallmark. Hence, our study's primary purpose is to explore the value of genes related to osteosarcoma metabolism. Methods From p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Our study has many highlights. Several researches previously have proposed certain risk signatures based on various characteristics, in hopes of stratifying the prognosis of cancer patients 53,54 . Zheng et al have identified a signature of seven‐lncRNA to predict the OS of patients with AML 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study has many highlights. Several researches previously have proposed certain risk signatures based on various characteristics, in hopes of stratifying the prognosis of cancer patients 53,54 . Zheng et al have identified a signature of seven‐lncRNA to predict the OS of patients with AML 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several novel assays such as lncRNAs have been developed. However, these methods are still some ways from clinical applications due to their high cost, difficulty in being obtained, and unified detection methods (42)(43)(44)(45). Meanwhile, the predictive effect of hematological markers has been widely explored.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is a rare type of cancer that affects the individuals of all ages including children ( Yang et al, 2021 ). However, because of the advancements in chemotherapy, precise radiotherapy, and immunotherapy, the overall 5-year overall survival (OS) rate of patients has substantially increased to 70% ( Li et al, 2021 ). It is noteworthy that only 15% to 20% of the patients were usually diagnosed with metastases, and the OS of these patients was reported to be extremely poor ( Durnali et al, 2013 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%